Transferring an Indigenous Practice for Soil Improvement : Cattle Manure with Groundnut Shells - World Bank (Washington, DC, 2012)
Soil fertility never used to be a major constraint due to the age-old practices of recycling agricultural residues in several ways. However, in these days of inorganic fertilizers and quick returns, the problem of soil management and its related constraints are surfacing. In this context, indigenous practices related to soil and water conservation which can also be termed resource-conserving technologies need to be documented in a systematic way and also to be analyzed and introduced to potential new areas. Preparation of valuable manure from groundnut shells spread on the floor of the cattle shed is one such indigenous practice followed by farmers of Anantapur district in the state of Andhra Pradesh in India. This age-old practice is still practiced by the farmers of this region.